Functional consequences of Rett syndrome mutations on human MeCP2 - Yusufzai, Timur M. (Oxford University Press, 2000)
The neurodevelopmental disorder known as Rett syndrome has recently been linked to the methyl-CpG-binding transcriptional repressor, MeCP2. In this report we examine the consequences of these mutations on the function of MeCP2. The ability to bind specifically to methylated DNA and the transcription repression capabilities are tested, as well as the stability of proteins in vivo. We find that all missense mutations (R106W, R133C, F155S, T158M) within the methyl-binding domain impair selectivity for methylated DNA, and that all nonsense mutations (L138X, R168X, E235X, R255X, R270X, V288X, R294X) that truncate all or some of the transcriptional repression domain (TRD) affect the ability to repress transcription and have decreased levels of stability in vivo. Two missense mutations, one in the TRD (R306C) and one in the C-terminus (E397K), had no noticeable effects on MeCP2 function. Together, these results provide evidence of how Rett syndrome mutations can affect distinct functions of MeCP2 and give insight into these mutations that may contribute to the disease.